PEMEROLEHAN BAHASA PADA ANAK AUTIS: KAJIAN PSIKOLINGUISTIK - Hikmawati, Yaumil; Patriantoro, Patriantoro; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is motivated by the attentiveness of researchers to find out how the development of a child with autism develops before or after doing research. Researchers saw firsthand how the attitude of compliance with Wilson's autistic children in speaking skills, how to form eye contact with autistic children Wilson in speaking skills, and how to shape responses to commands and calls to people with autistic Wilson's speaking skills. The study directly observed ABK activities following therapy classes using the ABA method, as well as increasing the skills of autistic children.Based on data analysis in this study, it can be concluded: 1) The ability to read pictures of children with autism mental age of 6 years can be grouped into three, namely, the ability to read nouns, verbs and adjectives. 2) The ability of children to count for children with autism mental age of 6 years through pictorial card media can be grouped into three, namely, the ability to count, recognize numbers and sort numbers.. 3) Therapy for the ability to read pictures and children's abilities to count for children with autism, starting from preparation by preparing a room, preparing a number card, preparing an image card, ball and rooting and preparing the mental and psychological children to learn. Keywords:language acquisition, children with special needs, abilitiesread and count